Nonalcoholic Fatty Liver Disease-Related Chronic Kidney Disease - Camelia Cojocariu; Ana-Maria Singeap; Irina Girleanu; Stefan Chiriac; Cristina M. Muzica; Catalin Victor Sfarti; Tudor Cuciureanu; Laura Huiban; Carol Stanciu; Anca Trifan (Canadian Journal of Gastroenterology and Hepatology)
Nonalcoholic fatty liver disease has become the main concern of hepatologists around the world and the main research topic for identifying effective and safe therapy. Advances in the treatment of chronic viral hepatitis in recent years have opened the way towards reducing mortality in patients with chronic liver disease. This goal has not yet been reached, as the burden of chronic liver disease remains a future major health problem as the incidence of the nonalcoholic fatty liver disease continues to rise. The proportion of patients with liver cirrhosis and those with hepatocellular carcinoma due to nonalcoholic liver disease on the liver transplant waiting list has increased in the last years. The upward trend in the incidence and prevalence of the disease in recent decades raises concern over a possible global epidemic, especially as the disease is still underestimated and underdiagnosed. Chronic kidney disease presented an increase in incidence and prevalence during the last years, and it has been associated not only with increased morbidity and mortality but also with high costs for the health system. During the last decade, several studies have shown the association between nonalcoholic fatty disease and chronic kidney disease, two major worldwide health problems.